2018
DOI: 10.1007/978-3-319-91602-6_7
|View full text |Cite
|
Sign up to set email alerts
|

Automated Acceptance Tests as Software Requirements: An Experiment to Compare the Applicability of Fit Tables and Gherkin Language

Abstract: Abstract. It is estimated that 85% of the defects in the developed software are originated from ambiguous, incomplete and wishful thinking software requirements. Natural language is often used to write software requirements specifications as well as user requirements. However, natural language specifications can be confusing and hard to understand. Some agile methodologists consider that acceptance tests are more precise and accurate sources of information about the customer's needs than descriptions in natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…An experiment on comparing text-based AATs and FIT tables revealed that text-based AATs are easier to understand. These tests are developed in shorter duration as compared to FIT tables [31].…”
Section: Automated Acceptance Tests (Aats)mentioning
confidence: 99%
“…An experiment on comparing text-based AATs and FIT tables revealed that text-based AATs are easier to understand. These tests are developed in shorter duration as compared to FIT tables [31].…”
Section: Automated Acceptance Tests (Aats)mentioning
confidence: 99%
“…Focusing on such state-of-practice, the most common strategies in agile testing are Test-Driven Development (TDD), Acceptance-Test-Driven Development (ATDD), and Behavior-Driven Development (BDD) [19]. Acceptance tests are expressed as code (e.g., using the Gherkin language [20]), creating an executable bridge between the user stories they are validating the implemented product. Solís and Wang advocate that ATDD is widely adopted in the industry because it im-proves software quality and productivity [21].…”
Section: Related Workmentioning
confidence: 99%
“…In the agile software development, acceptance tests are adopted to enable the communication and collaboration among the stakeholders [1,2,3]. Some agile developers, users and clients use acceptance testing as a way of specifying software requirements instead of using only common artifacts based on natural language [17,18]. This is an attempt to improve the quality of requirements because several problems can arise when requirements are written in natural language, for example, readers and writers can use the same word for different concepts, or express the same concept in completely different ways [18].…”
Section: Introductionmentioning
confidence: 99%